New Frontiers for Decommissioning in Brazil - Leite, Barbara Eiroa; Belchior, Bruno (Journal of Sustainable Development Law and Policy, 2025)
This article explores the challenges and opportunities for decommissioning in Brazil, presenting the relevant regulatory framework. It also highlights the importance of the sustainable development as one of the guiding principles for the Brazilian government, especially to the energy sector. In this sense, the article explores different methods of infrastructure decommissioning, including the most advanced ones, such as the reuse to create wind offshore power projects or artificial reefs. Overall, the article discusses the expectations and forecasts for decommissioning activities in Brazil, and concludes that they have the potential to become a key instrument for the country to preserve the environment.